Increasing Growth and yield of cucumber (Cucumis sativus L.) by applying baglog waste compost and manure in sand soil and paddy soil combination media - Ristiyana, Suci; Saputra, Tri Wahyu; Subroto, Gatot; Setiyono, Setiyono (Jurnal Agrotek Ummat, 2023)
One of the causes of low productivity in cucumber plants is due to low soil quality due to low organic matter content and high sandy soil mixture. Considering this, it is necessary to try to improve it. So, there is a need for research that examines the addition of organic matter and combines sandy media with paddy soil.This research took place in Pecoro Village, Jember Regency from May 2022 to July 2022. The research method was in the form of a Completely Randomized Design with the first treatment, namely the addition of baglog waste compost and cow manure (K1); baglog waste compost and goat manure (K2); and compost baglog waste and chicken manure (K3). While the second treatment is sandy planting media consisting of: sand 100% (M0); 75% sand + 25% paddy soil (M1); 50% sand + 50% paddy soil (M2); and 25% sand + 75% paddy soil (M3). The observed variables included plant height, total fruit weight, fruit unit weight, fruit length and fruit diameter which were tested by means of variance and Duncan's Multiple Range test.The results showed that the treatment of compost, sandy planting media, and their interactions had a significant effect on the observed variables. The recommendations given based on the results of the analysis for cucumber cultivation are the need to add organic matter such as compost mixed with baglog waste and manure from cow, goat and chicken manure with a ratio of 25% sandy planting medium to 75% paddy soil.